DEDIFFERENTIATED LEIOMYOSARCOMA - Anggie Sasmita Kharisma Putri; Diah Prabawati Retnani; Aina Angelina; Harun Al Rasyid; Karyono Mintaroem; Eviana Norahmawati; M Luqman Fadli (Universitas Hang Tuah, 2023)
Background: Meningioma is the most common intracranial tumor in adults. Progesterone plays a role in the cell development and proliferation of hormone-associated tumors, such as meningiomas. Significant morbidity and mortality can occur, when the lesion is localized in an area that is difficult to undergo surgical resection or is highly infiltrative in the surrounding tissue. Many studies have been published on the molecular properties associated with meningioma aggressive behavior, including matrix metalloproteinase (MMP), but research on the relationship between PR expression and MMP-9 has not been widely carried out. Methods: This study used a cross-sectional analytic observational study design. The analysis used in this study includes descriptive analysis and bivariate analysis. The data obtained was processed using SPSS software. Results: Spearman's correlation test for PR expression with WHO grading in meningioma, obtained p = 0.492 and correlation coefficient -0.117. This shows a correlation that is not significant. Spearman's correlation test for MMP expression with WHO grading in meningioma, obtained p = 0.16 and a correlation coefficient of 0.236. This shows a correlation that is not significant. Spearman's correlation test between MMP9 expression and WHO grading in meningioma obtained p = 0.008 which indicated that the correlation between PR and MMP9 values ​​was significant with a correlation value of -0.427. Conclusion: There is no significant correlation between PR expression and WHO grading. There was no significant correlation between MMP9 expression and WHO grading. There is a significant correlation between PR expression and MMP9.